(untitled) (Research, Society and Development, 2021)
The objective was to describe the quality of the primary health care (PHC) according to male users. This is an evaluative and cross-sectional study in which 228 men were interviewed at home, from February to July of 2019, in areas of eight Family Health Strategies in a municipality in Minas Gerais. The resources Google Forms (reduced version of PCATool), Excel, SPSS and R were used. Pearson’s chi-square, Fisher’s Exact and Mann-Whitney tests were used, at a significance level of 5%. The participants profiled as elderly, mixed race, born in other cities, who lived with one more person, married, educated from the first to the fourth grade of elementary school, retired and with income from 1.5 up to 3 minimum wages. Self-reports of hypertension, diabetes, alcohol use, kidney disease and mental health problem were highlighted. Among the interviewees, 80.70% rated the PHC as of low quality. There was association between having hypertension and the quality of the PHC (p = 0.001). Thus, the objectives of this study were achieved, emphasizing the poor quality of PHC in the view of men belonging to socially vulnerable groups and the need to expand the access of young men to the PHC.